2019
DOI: 10.1182/blood.2019000658
|View full text |Cite
|
Sign up to set email alerts
|

Timing of inhibitor development in more than 1000 previously untreated patients with severe hemophilia A

Abstract: Diagnosis of amyloidosis, with the possible exception of cardiac transthyretin amyloidosis (ATTR) in patients without monoclonal components, 1 requires demonstration of tissue amyloid deposits and identification of the amyloidogenic protein. 2,3 The gold standard for amyloid detection is Congo red (CR) staining, based on amyloid's congophilia and birefringence under polarized light (PL; CR-PL). 4 When systemic amyloidosis is suspected, subcutaneous abdominal fat, acquired by fine-needle aspiration or punch bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 19 publications
2
60
0
Order By: Relevance
“…A subgroup especially relevant to post-marketing surveillance are PUPs, as with the end of mandatory clinical trials in PUPs with hemophilia, post-marketing data captured in hemophilia registries will become increasingly important to optimize hemophilia treatment for PUPs as compared to PTPs. One major difference between PUPs and PTPs is inhibitor risk, which is highest in PUPs just beginning treatment and much lower in PTPs [ 58 , 59 , 60 , 61 , 62 , 63 ]. To ensure relevance and completeness of patient data captured in this early stage of treatment, the dhr was harmonized with the designated PUP registries PedNet and GEPHARD.…”
Section: Resultsmentioning
confidence: 99%
“…A subgroup especially relevant to post-marketing surveillance are PUPs, as with the end of mandatory clinical trials in PUPs with hemophilia, post-marketing data captured in hemophilia registries will become increasingly important to optimize hemophilia treatment for PUPs as compared to PTPs. One major difference between PUPs and PTPs is inhibitor risk, which is highest in PUPs just beginning treatment and much lower in PTPs [ 58 , 59 , 60 , 61 , 62 , 63 ]. To ensure relevance and completeness of patient data captured in this early stage of treatment, the dhr was harmonized with the designated PUP registries PedNet and GEPHARD.…”
Section: Resultsmentioning
confidence: 99%
“…Among patients who do develop inhibitors, ∼70% of those who then receive ITI therapy achieve peripheral immune tolerance to FVIII, which is defined operationally as an inhibitor titer below 0.6 Bethesda units/mL (18,19). Many inhibitors develop within the first 20 FVIII infusions, following a classic prime + boost pattern (20), while inhibitor development after 50 FVIII exposure days is rare (21,22). Inhibitor development requires uptake, processing and MHC Class II presentation of FVIII peptides and subsequent recognition of the peptide-MHC Class II complexes by circulating T cells (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In the PedNet registry, patients were followed for up to 1000 exposure days. Recently published data showed that 79% of all inhibitors developed within 20 exposure days and 18% between 20 and 50 exposure days 16 …”
Section: Discussionmentioning
confidence: 99%
“…As of January 2018, the PedNet Haemophilia Registry had included 1035 patients with severe haemophilia A (factor VIII activity at baseline percentage ≤1%) from 31 haemophilia centres (http://www.pednet.eu, http://www.clinicaltrials.gov trial no: NCT02979119) 16,17 . To provide a contemporaneous comparison to the clinical study, we selected all PUPs treated with human recombinant FVIII octocog alfa who were born between 2000 and 2009.…”
Section: Methodsmentioning
confidence: 99%